Watching North Korea from the sky: Remote sensing and documenting human rights in the Democratic People's Republic of Korea. (January 2022) - Son, Sarah A.
Abstract: For organisations committed to documenting human rights abuses in North Korea, gathering data is an ongoing challenge. Faced with the lack of access to the country, as well as the problems inherent in verifying testimonies from North Korean escapees, some organisations have turned to hybrid methodologies, including pairing remote sensing (RS) technologies with testimonial data to better understand the people, places and institutions associated with human rights violations. In the case of North Korea, to date, remote sensing has been used primarily to monitor nuclear weapons and missile development sites. This work has at times sparked controversy, given the scope for analytical error and the high stakes associated with flawed analysis. Against this backdrop, this article discusses the application of remote sensing to augment human rights abuse investigations and calls for greater attention to the potential of remote sensing data to both assist in eliciting information in research interviews, and to generate data that may be used to support the pursuit of accountability for alleged violations of international law. Specifically, it considers the work of an ongoing project developed in South Korea using satellite imagery and Geographic Information Systems technology together with witness testimonies to document sites of state-led killings and burials in North Korea. The paper cites advantages to be had from developing hybrid methods of data-gathering in this context and describes some of the key methodological considerations involved, as well as the possible applications of the data in seeking justice and remedy in the future.